Factors Influencing the Implementation of Non‐Pharmacological Interventions for Behavioural and Psychological Symptoms of Dementia in Residential Aged‐Care Homes: A Systematic Review and Qualitative Evidence Synthesis: A systematic review - Hunduma Dinsa Ayeno; Gizat M. Kassie; Mustafa Atee; Tuan Nguyen (Campbell Systematic Reviews)
ABSTRACT Background Non‐pharmacological interventions (NPIs) are the primary approaches to the management of behavioural and psychological symptoms of dementia (BPSD), but studies have indicated that there is a suboptimal implementation. Although there are several studies on the factors influencing NPI implementation for BPSD at residential aged‐care homes (RACHs), there has not been a comprehensive qualitative systematic review on the topic. Objectives This systematic review aimed to examine the qualitative studies that investigate the factors influencing the implementation of NPIs for managing BPSD in RACHs. Search Methods Systematic searches were conducted up until 31 December 2023 using five databases: MEDLINE, EMCARE, EMBASE, CINAHL complete and APA PsycINFO. Selection Criteria This systematic review included qualitative studies and qualitative data from mixed‐method studies on the implementation of NPIs for RACH residents with dementia experiencing BPSD. The research question and inclusion criteria for this review included the components of PICo: Population (aged‐care residents with dementia), Phenomenon of interest (factors influencing implementation of NPIs) and Context/setting (RACHs). Data Collection and Analysis After screening and extracting the data, the methodological limitations were assessed using the Joanna Briggs Institute System for the Unified Management, Assessment, and Review of Information (JBI SUMARI) quality assessment tool. JBI SUMARI meta‐aggregative synthesis was used to synthesise the data. The extracted findings were categorised into the 10 Theoretical Domain Framework domains: knowledge, skills, environmental context and resources, social influences, reinforcement, emotions, intentions, beliefs about consequences, social and professional roles and beliefs about capability. Confidence in the output of qualitative research synthesis (CONQual) was used to assess the credibility and dependability of the synthesised findings. Main Results Twenty‐four studies were included, from which factors influencing NPI implementation were extracted. Study participants included RACH managers, RACH care staff, families of aged‐care residents with dementia and volunteers. Amongst the studies specifying the gender of participants, there were 352 females (84.4%) and 46 males (15.6%). The method of data collection for the included studies consisted of eighteen interviews, five focus group discussions and one qualitative survey. All except one study had a quality assessment score of at least 60% based on the JBI SUMARI quality assessment tool. However, all studies were included regardless of the result of the quality assessment result. These studies spanned the period from 2010 to 2022 and were mostly conducted in the United Kingdom, Australia, the United States and Canada. Twenty‐four synthesised findings were identified (13 high, 7 moderate and 4 low ConQual scores). Examples of factors influencing the implementation of NPIs were collaboration amongst care staff and families of residents with dementia, belief in the efficacy of interventions, staffing, staff time constraints, funding, familiarity with the interventions, organisational support, communication amongst the care staff and with families of residents with dementia, education and training for the care staff and families of residents with dementia and familiarity with the residents with dementia. Authors' Conclusions This systematic review highlights and synthesises factors influencing the implementation of NPIs for managing BPSD in RACHs. Key factors include collaboration amongst staff and families, organisational support, staffing, education and staff familiarity with both the interventions and residents. Strengthening these areas could enhance the care outcomes for aged‐care residents with dementia. For decision‐makers, these insights suggest the need for comprehensive strategies to improve NPI implementation. This could include ensuring appropriate staffing levels, enhancing collaboration, allocating adequate funds, providing training, strengthening organisational support and improving the quality of information exchange amongst care staff, between care staff and volunteers and families of residents with dementia. For researchers, the findings from this systematic review could provide valuable insights including the need to explore strategies to overcome barriers to NPI implementation, especially investigating innovative models for staffing and collaborative practice, examining the effectiveness of different education and training approaches, and exploring organisational policies and support mechanisms that can enhance the implementation of NPIs.